2016
DOI: 10.1016/j.watres.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Microbial fuel cells and osmotic membrane bioreactors have mutual benefits for wastewater treatment and energy production

Abstract: This study demonstrates that microbial fuel cells (MFCs) and osmotic membrane bioreactors (OMBRs) can be mutually beneficial when integrated together for wastewater treatment. When connecting MFCs with OMBRs, the solute buildup increased conductivity and buffer capacity, which greatly increased MFC power density from 3 W/m(3) up to 11.5 W/m(3). In turn, the MFCs conditioned and reduced sludge production and therefore reduced forward osmosis (FO) membrane fouling. The MFC-OMBR equipped with new thin-film compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 54 publications
2
33
2
Order By: Relevance
“…Nevertheless, standalone treatment system has limitation such as less wastewater treatment efficiency as compared to the MFC hybrid system [7]. Much studies had demonstrated the ability of hybrid MFCs in removing various types of pollutants present in the wastewater such as chemical oxygen demand (COD) [8][9][10], phosphorus [11], dye [12,13], suspended solids (SS) [10], total nitrogen (TN) [14], ammonia nitrogen (NH 3 À ÀN) [15,16], and so on. Majority of the effective pollutants removal were done by integrating MFC with other unit operation or processes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, standalone treatment system has limitation such as less wastewater treatment efficiency as compared to the MFC hybrid system [7]. Much studies had demonstrated the ability of hybrid MFCs in removing various types of pollutants present in the wastewater such as chemical oxygen demand (COD) [8][9][10], phosphorus [11], dye [12,13], suspended solids (SS) [10], total nitrogen (TN) [14], ammonia nitrogen (NH 3 À ÀN) [15,16], and so on. Majority of the effective pollutants removal were done by integrating MFC with other unit operation or processes.…”
Section: Introductionmentioning
confidence: 99%
“…This cooperation can also create mutual benefits that strengthen each of the unit in this system ( Figure 2.4). As mentioned earlier, an OMBR and an MFC could benefit each other in terms of enhancing electricity generation and reducing membrane fouling (Hou et al 2016). Enhancing electricity…”
Section: Mutual Benefitsmentioning
confidence: 98%
“…An example of a coupled OsBES is to connect an MEC to an FO unit for recovering ammonium from a synthetic wastewater and then applying the recovered ammonium as a draw in the subsequent FO process He 2014, Qin et al 2016b). In an osmotic membrane bioreactor (OMBR) -MFC system, the membrane fouling in the OMBR was alleviated by the MFC treatment, and the electricity generation in the MFC was enhanced due to increased solution conductivity after the OMBR treatment (Hou et al 2016). FO-based processes have also been studied as pre-treatment before BES.…”
Section: Osmotic Bioelectrochemical Systemsmentioning
confidence: 99%
See 2 more Smart Citations